2016
DOI: 10.1038/nchem.2471
|View full text |Cite
|
Sign up to set email alerts
|

Charge-compensation in 3d-transition-metal-oxide intercalation cathodes through the generation of localized electron holes on oxygen

Abstract: During the charging and discharging of lithium-ion-battery cathodes through the de- and reintercalation of lithium ions, electroneutrality is maintained by transition-metal redox chemistry, which limits the charge that can be stored. However, for some transition-metal oxides this limit can be broken and oxygen loss and/or oxygen redox reactions have been proposed to explain the phenomenon. We present operando mass spectrometry of (18)O-labelled Li1.2[Ni0.13(2+)Co0.13(3+)Mn0.54(4+)]O2, which demonstrates that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

56
1,006
4
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,027 publications
(1,073 citation statements)
references
References 50 publications
56
1,006
4
7
Order By: Relevance
“…While some groups expect electrochemical activation of Li 2 MnO 3 to MnO 2 accompanied by bulk oxygen release, 11 more recent publications give strong evidence that anionic oxygen redox might serve for charge compensation at high delithiation. 26,[31][32][33] The specific role of oxygen release HE-NCM particularly during the first activation cycle will be analyzed and discussed later on.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While some groups expect electrochemical activation of Li 2 MnO 3 to MnO 2 accompanied by bulk oxygen release, 11 more recent publications give strong evidence that anionic oxygen redox might serve for charge compensation at high delithiation. 26,[31][32][33] The specific role of oxygen release HE-NCM particularly during the first activation cycle will be analyzed and discussed later on.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 At first sight, this seemed consistent with the mass spectrometrically detected O 2 and CO 2 evolution starting during the activation plateau, which was interpreted to indicate the release of Li 2 O from the bulk of the material during activation and accompanying structural changes within the bulk material. 15,17,18,23,24 However, the exact quantification of the released oxygen by Strehle et al and Luo et al revealed that the amount of released oxygen is an order of magnitude too low to be consistent with the assumed electrochemical oxygen release 25,26 and also that the O 2 evolution does not start until right after the activation plateau (only <10 μmol O2 /g AM during the plateau, but >100 μmol O2 /g AM following thereafter; shown by Strehle et al). 25 Both observations suggested that the observed oxygen release cannot be ascribed to a loss of oxygen from the bulk of the material, but that the oxygen is only being released from the near-surface Thus, more recent studies propose that bulk and surface of these overlithiated materials show distinctly different properties, rationalized by a bulk-shell model.…”
mentioning
confidence: 99%
“…In order to find out more detailed information about the electronic structure of the nanosheets on the surface and in the bulk, the X-ray Absorption Near Edge Structure (XANES) spectroscopy was employed, since the XANES data can be recorded simultaneously in both total electron yield mode (TEY) and fluorescence yield mode (TFY) with different probing depth. [40][41] Total electron yield mode probes the surface information with a depth ∼ 5nm, while the data collected in the fluorescence yield mode provides the information from the bulk with a probing depth of ∼ 50 nm. Normalized XANES at Co L-edge and O K-edge are shown in Figure 2a and 2b, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Making high‐voltage TMOs viable requires increasing the reversible potential window through understanding the high‐voltage instabilities of intercalation materials and electrolytes 1. Much recent work has revealed an intimate interdependence of electrolyte decomposition, surface species formation/decomposition, and TMO bulk and surface reconstruction 2d, 3d, 5. In particular, it was recently found that the outgassing of CO 2 during the first cycle in Li‐ion batteries is mostly governed by residual Li 2 CO 3 , which in turn affects O 2 evolution from the TMO lattice 5b.…”
mentioning
confidence: 99%